PEMBUATAN E-COMMERCE PRODUK KOPI KAMPUNG STAMPLAT, DESA INDRAGIRI, KABUPATEN BANDUNG - Deni Setiawan; Jimmy Agustian Loekito; Yosafat Pranata (Servirisma, 2022)
Kampung Stamplat has potential in the form of coffee produced from community coffee plantations. Based on information from the head of the hamlet, the coffee marketed under the name Kopi Djamuju. Coffee plants thrive in this area, the taste and quality of Djamuju coffee is not inferior to other coffees. Coffee farmers in this village carry out the traditional process of seeding, planting, maintaining plants and harvesting coffee beans. Marketing of coffee beans is also carried out by utilizing other parties, thus this condition makes farmers sell coffee beans with low profits. The purpose of community service activities in this paper is the creation of e-commerce for the sale of coffee products produced by residents of Kampung Stamplat, Dusun Ciparay, Indragiri Village, Rancabali District, Bandung Regency. The scope of activity consists of two stages, with the first stage being the creation of an online store on several startup platforms along with an online store management module and the second stage being counseling on the use of applications and online store management modules specifically for the youth youth of Kampung Stamplat. The results of the activities in the first stage were technical discussions with the Head of Indragri Village and Head of Dusun Ciparay and representatives of the local Karang Taruna management on 9 June 2021 it was concluded that Djamuju coffee products were the main product of Stamplat Village which is part of Ciparay Hamlet. Then followed by technical discussions on 1 August 2021, an agreement was obtained that training and socialization of the use and management of e-commerce will be carried out after the implementation of the Restrictions on Community Activities is completed so as to allow a limited number of meetings. The target of the second stage is that the existence of e-commerce can increase sales compared to before. The results of the activities presented in this scientific paper are prototypes of shops made on e-commerce platforms